The devil is a part-timer! 17 - Wagahara, Satoshi (The devil is a part-timer (graphic novels), 2021)
"Maou and Suzuno drive their scooters across Ente Isla on a journey to save their kidnapped friends. However, time is running short, as Emilia and Ashiya have been forced to reassume their roles as Hero and demon general, setting the stage for a fight to the death! With the decisive battle looming, it's all up to Maou to rescue them, but what's wrong with his powers at this critical moment ...?"--